Quality of the cysts of Artemia franciscana collected at Tuticorin with observations on growth, maturity and sex ratio of the offspring - Rajamani, M; Kumar, S Asok; Maharajan, S Vimala (Indian Journal of Fisheries, 2011)
The cysts of the exotic species of brine shrimp Artemia franciscana collected from the natural ecosystem at Tuticorin during January 2001 were processed, stored and their quality evaluated. A total of 22 experiments were conducted on hatching and it was observed that the time taken for first hatching ranged from 13 hours and 10 minutes to 17 hours. The maximum hatching percentage recorded at 24 hours and 48 hours were 52.0 and 79.9 respectively. The I instar obtained from the hatching experiments were reared in outdoor culture tanks at 30, 50, and 70 ppt with two different types of feed and the maximum size of 10.04 Â± 0.3 mm was recorded on 18th day in the animals fed with rice bran at 70 ppt. The earliest first pairing and first spawning were recorded on 6th and 12th days respectively in the animals fed with mixed phytoplankton at 50 ppt.